Mass transfer enhancement and improved nitrification in MABR through specific membrane configuration. (1st April 2019) - Castrillo, M.; Díez-Montero, R.; Esteban-García, A.L.; Tejero, I.
Abstract: One of the main energy consumptions in wastewater treatment plants (WWTPs) is due to the oxygenation of aerobic biological processes. In order to approach to an energy self-sufficient scenario in WWTPs, Membrane Aerated Biofilm Reactors (MABRs) provide a good opportunity to reduce the impact of aeration on the global energy balance. However, mass transfer limitations derived from poor flow distribution must be tackled to take advantage of this technology. In this work, in order to improve mass transfer between biofilm and bulk water, a specific configuration was developed and studied at laboratory scale, aimed at compactness, energy efficiency and high nitrification rates. Nitrification rates were higher in the innovative configuration than in the conventional one, achieving a Volumetric Nitrification Rate (VNR) as high as 575.84 g NH4 -N m −3 d −1, which is comparable with confirmed technologies. Regarding energy consumption due to aeration, a reduction of 83.7% was reached in comparison with aeration through diffusers with the same Oxygen Transfer Efficiency (OTE). These results highlight the importance of hydrodynamic conditions and the membranes configuration on treatment performance. Graphical abstract: Image 1 Highlights: A high packing MABR configuration enhances flow pattern and mass transfer. Volumetric nitrification rates comparable to confirmed technologies are achieved. A reduction of 83.7% in energy consumption is reached in comparison with diffusers. Membranes configuration and recycling velocity influence biological performance.